Analysis of uranium and other water quality parameters in drinking water sources of 5 districts of Kerala in southern India and potability estimation using water quality indexing method - C.S. Shalumon (KeAi Communications Co., Ltd., 2021)
An analysis on the presence of uranium in drinking water sources of five districts in Kerala, Southern India has been carried out. 830 Samples from different sources during pre and post-monsoon seasons were subjected to the analysis for uranium and 11 other water quality parameters. The concentration of uranium was found to be varying from <0.5–12.54 μg/L in pre-monsoon and <0.5–5.93 μg/L in post-monsoon which is well within the standard limit i.e. 30 μg/L. Water Quality Indexing analysis shows that only less than 10% of the samples are unsuitable for drinking purpose. From the present study, it is clear that the current drinking water sources used by the public in the study area contain no or very low concentration of U and the overall water quality is satisfying the potability requirements and it is suitable for drinking water purpose.